Pillar with purna kalasha and kalpa lata motifs and a broken amalaka - Temples of India Project Team (Jio Institute, 2024)
Debris from the original temple was salvaged when the current temple was reconstructed in the 1940s. These have been assembled in parts to form the jagati (raised platform). This vertical fragment is topped with a broken amalaka (notched disc). However, it is not known where they were located in the original temple. A broken section of the block features two pillars divided vertically in three sections. The kalpa lata (creeper) motif features at the base, the purna kalasha (pot of prosperity) in the central part. The top part is damaged and blooming lotuses separate the three parts. In the central part, a flowing kalpavrisksha (tree of life) motif is carved in great detail.